Team perfectionism and team performance: A prospective study - Hill, A. P.; Stoeber, J.; Brown, A.; Appleton, P. R. (Journal of Sport & Exercise Psychology, 2014)
Perfectionism is a personality characteristic that has been found to predict sports performance in athletes. To date, however, research has exclusively examined this relationship at an individual level (i.e., athletes` perfectionism predicting their personal performance). The current study extends this research to team sports by examining whether, when manifested at the team level, perfectionism predicts team performance. A sample of 231 competitive rowers from 36 boats completed measures of self-oriented, team-oriented, and team-prescribed perfectionism before competing against one another in a 4-day rowing competition. Strong within-boat similarities in the levels of team members` team-oriented perfectionism supported the existence of collective team-oriented perfectionism at the boat level. Two-level latent growth curve modeling of day-by-day boat performance showed that team-oriented perfectionism positively predicted the position of the boat in midcompetition and the linear improvement in position. The findings suggest that imposing perfectionistic standards on team members may drive teams to greater levels of performance.